Panchromatic (Sub)millimeter polarization observations of HL Tau unveil aligned scattering grains - Lin, Zhe Yu Daniel (2024)
Polarization is a unique tool to study the dust grains of protoplanetary discs. Polarization around HL Tau was previously imaged using the Atacama Large Millimeter/submillimeter Array (ALMA) at Bands 3 (3.1 mm), 6 (1.3 mm), and 7 (0.87 mm), showing that the polarization orientation changes across wavelength λ. Polarization at Band 7 is predominantly parallel to the disc minor axis but appears azimuthally oriented at Band 3, with the morphology at Band 6 in between the two. We present new ~0.2 arcsec (29 au) polarization observations at Q-Band (7.0 mm) using the Karl G. Jansky Very Large Array (VLA) and at Bands 4 (2.1 mm), 5 (1.5 mm), and 7 using ALMA, consolidating HL Tau´s position as the protoplanetary disc with the most complete wavelength coverage in dust polarization. The polarization patterns at Bands 4 and 5 follow the previously identified morphological transition with wavelength. From the azimuthal variation, we decompose the polarization into contributions from scattering (s) and thermal emission (t). s decreases slowly with increasing λ, and t increases more rapidly which are expected from optical depth effects of toroidally aligned scattering prolate grains. The weak λ dependence of s is inconsistent with the simplest case of Rayleigh scattering by small grains in the optically thin limit but can be affected by factors such as optical depth, disc substructure, and dust porosity. The sparse polarization detections from the Q-band image are also consistent with toroidally aligned prolate grains.